ANALYSIS OF DEVICES USED IN THE CRUSHING OF SOLID COMPONENTS IN THE CRUSHING OF INDUSTRIAL WASTE (E Conference Zone, 2022)
After briquetting, the coal particles are converted into a semi-finished product, a finished product, and a raw material designed to accelerate a process or to carry out a process. Fuel briquettes also have very positive storage properties, take up relatively little space and do not sit in the working area of machinery; dust-free during transportation and packaging, which in turn helps to prevent product waste at all stages; ensures the safety of the working environment, especially when working with flammable substances; increases accuracy by facilitating quantification in a variety of processes.